IN DEFENSE OF THE ACCOUNTANT. - Kelley, Arthur C. (The Accounting Review, 1936)
Abstract Economists often take the accountants to task for loose thinking, failure to define their terms, not comprehending the nature of income, and in general for being concerned primarily with procedure instead of with the development of a consistent philosophy of accounting. No doubt much of this criticism is justified and there is much need of a more careful use of words and more precise definitions of accounting terms in the writings of accountants. The fact is that many of the writings of economists disclose such a theoretical and academic type of mind, that their ideas are of very little help to the accountant in solving the problems which face him in his daily practice. A school of economic thought has arisen which has developed and elaborated the idea that the work of the accountant is essentially that of valuation, and the balance sheet is in essence a statement showing the present worth's of the expected future services which the assets will yield. The balance sheet is thus a forecast and is not an objective statement of facts. The accountant becomes a forecaster and prepares statements of opinion about what will happen in the future. This idea is surely far removed from the realities of the accountant's daily work.